TYPIFICATION OF GEOMETRIC SHAPES OF TRUSSES AND THEIR LATTICES - Омелян, Максим (SWorldJournal, 2024)
The paper studies the typification of geometric forms of trusses and their lattices, which are an important component of modern building structures. The main attention is paid to the analysis of different types of trusses, their structural elements and g